2021
DOI: 10.1039/d1ra01391b
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic synthesis of novel fructosylated compounds by Ffase from Schwanniomyces occidentalis in green solvents

Abstract: Glycerol, as a good acceptor for Ffase, produces novel fructosylated derivatives with biotechnological potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 54 publications
(96 reference statements)
0
2
0
Order By: Relevance
“…[46][47][48][49] It is also interesting to analyse the ecotoxicity of the studied DES by comparing with their components separately, and specially to the corresponding glycerol-derived ethers, also used as green solvents. 50 It has been described that the toxicity of the starting materials of DES varies comparing with their derived eutectic mixture. Macário et al carried out a predictive test for ChCl mixtures in which DES showed less toxicity than their starting materials individually.…”
Section: A Fischeri Ecotoxicity Testmentioning
confidence: 99%
“…[46][47][48][49] It is also interesting to analyse the ecotoxicity of the studied DES by comparing with their components separately, and specially to the corresponding glycerol-derived ethers, also used as green solvents. 50 It has been described that the toxicity of the starting materials of DES varies comparing with their derived eutectic mixture. Macário et al carried out a predictive test for ChCl mixtures in which DES showed less toxicity than their starting materials individually.…”
Section: A Fischeri Ecotoxicity Testmentioning
confidence: 99%
“…In contrast, enzymatic glycosylation has attracted extensive interest because of its exquisite selectivity and mild reaction conditions. 15,16 There are two types of enzymes used for glycosylation: glycosyltransferases and glycosidases. 17,18 Glycosyltransferases catalyze the formation of glycosidic bonds needed to supply an activated sugar donor, such as uridinediphosphate glucose (UDP-G), which constrained its practical application.…”
Section: Introductionmentioning
confidence: 99%